The portrayal of the Philippine policemen by GMA and ABS-CBN news online (2015 to 2017) - Gargoles, Katrina Collado (2018)
"This thesis examines the online news portrayal of the Philippine National Police in the online news sites of country's leading television networks. This study looked into the news articles published in GMA and ABS-CBN news online sites from January 2015 to December 2017. Quantitative research design, particularly content and textual analysis, is used to analyze the recurring themes or topics of news stories involving police, and the different portrayals of the policemen and the PNP from 2015 to 2017. The research considered the media as a significant factor in shaping public opinion and perception. Thus, the news media, as noted in this study, is a primary source of crime reports that generally offer a conflicting portrayal of police as heroic and professional crime fighters, while simultaneously portraying police as abusive, corrupt and law-abider. Through this study, the researcher aims to contribute empirical data to the current field of knowledge regarding policemen and media reporting in the local setting."